PENERAPAN STRATEGI MATH TRAIL UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA SISWA KELAS V SD INPRES 12/79 BULU TEMPE KABUPATEN BONE - Sudirman; Satriani; Maharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Math Trail strategy to improve the mathematical problem-solving ability of fifth-grade students at SD Inpres 12/79 Bulu Tempe, Bone Regency, and to determine whether the strategy can improve that ability. This research is a Classroom Action Research (CAR) using a qualitative approach, conducted in two cycles following the planning, acting, observing, and reflecting stages of the Kemmis and McTaggart model. The subjects were all 25 fifth-grade students, consisting of 14 boys and 11 girls, together with their homeroom teacher. Data were collected through observation sheets and problem-solving tests, then analyzed through data reduction, data display, and conclusion drawing. The results showed that teacher activity increased from 58.33% (fair) in cycle I meeting 1 to 79.17% (good) in cycle II meeting 2, while student activity increased from 57.33% (fair) to 80.5% (good). The problem-solving test results showed that 17 of 25 students (68%) reached the high or very high category in cycle I, increasing to 19 of 25 students (76%) in cycle II. All four problem-solving indicators based on Polya's stages also improved from cycle I to cycle II. It is concluded that the implementation of the Math Trail strategy can improve the mathematical problem-solving ability of fifth-grade students at SD Inpres 12/79 Bulu Tempe, Bone Regency.